Hubungan Pengetahuan Terhadap Pemanfaatan Obat Herbal Imunomodulator Di RT 24 Kelayan B - Rifqi, Muhammad; Kurniawati, Darini; Syamsu, Erlina (CV. Wadah Publikasi Cendekia, 2023)
Health can be interpreted as a basic need of every individual human being used in fulfilling his daily needs. There are several ways used as an effort to prevent disease, one of which is by increasing endurance. Immunomodulatory herbal medicine is one way to increase endurance by increasing the mechanism of the body's immune system either specifically or non-specifically. The RT 24 Kelayan B community has used immunomodulatory herbal medicines, but there have been those who have examined the relationship of knowledge to the use of immunomodulatory herbal medicines. The general objective of this study is to determine the relationship between the level of knowledge on the use of immunomodulatory herbal medicines in RT 24 Kelayan B. This type and design of study uses analytical observational method with Cross Sectional research design. The instrument used is a questionnaire. A total of 61 people (89.7%) had good knowledge and 59 people (86.8%) had a good utilization rate of herbal medicines. The variable that affects the use of immunomodulatory herbal medicines is knowledge with the results of analysis using the Sperman Rho Correlation test showing the results that the significance value obtained is 0.000 (< 0.05) and has a correlation coefficient value obtained of 0.534 in a positive direction. Based on the results of the study P value value 0.000 with a correlation coefficient of 0.534, it can be concluded that there is a relationship of knowledge to the use of immunomodulatory herbal medicines in RT 24 Kelayan B. Keywords: immunomodulator, herbal medicine, utilization, knowledge